Credit Risk Management Practices in Dashen Bank of Mettu Branch in Ethiopia - S.N. Singh (Financial Markets, Institutions and Risks)
Credit Risk management becomes major discussion issues in the financial institutions because of uncertainty related to borrower’s business. The aim of this study is to assess credit risk management tools and technique that are being used in the bank and to what extent the current performance of the bank is supported by proper credit risk management policy, procedure and strategy. The study design is descriptive. The research applies for both qualitative and quantitative research method and both primary data (questionnaire) and secondary data were collected to meet the objective of the study. 15 out of 20 total population Purposive samples were involved at Branch office using census sampling method who works on credit to get reliable and valid information about the study subject. The data was analyzed using qualitative and descriptive statistics technique and frequency table. From the findings the study concludes that the bank has well organized credit policy that counter to credit risk they are exposed to and it also conclude that the bank has good credit granting practice and uses suitable credit risk assessment tools and techniques including loan follow-up, risk identification, measuring, evaluating, monitoring and controlling mechanism. However, the study also concluded that the bank has pitfalls such as absence of training for customers which results to loan diversion, absence of credit risk model that predict the risk level of the business and the priority sectors of the bank in terms of credit facility are highly exposed to credit risk which directly contribute to the increment of NPL. Thus, it is recommended that Dashen Bank S.C should develop independent risk management policy and procedure from credit policy and procedure to overcome those problems and to take measure on the spot.